PENGEMBANGAN KEMANDIRIAN PEREMPUAN MELALUI PELATIHAN KEWIRAUSAHAAN BAGI IBU-IBU PKK KARANGWANGKAL - Yusyida Munsa Idah (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
Entrepreneurship activities can also be carried out by developing skills for entrepreneurs or prospective entrepreneurs. (1) Skill development for mothers who want to run entrepreneurship, one of which is sewing skills. In previous service activities, basic sewing training for women's clothing has been carried out, but if these skills are only basic, according to partners, basic sewing skills cannot be used as capital to run a sewing service business. The problems faced were due to limited time, so they could not directly conduct training in just one time. In this service, training was carried out with materials on advanced sewing, by repeating patterns, how to measure the body and the importance of making financial reports, even though the business/business was started from home. With this training, trainees gain knowledge about the importance of making financial reports, and have the skills to measure the body for dress sizes, make patterns and sew women's clothes.